2016
DOI: 10.1074/jbc.m116.738930
|View full text |Cite
|
Sign up to set email alerts
|

Male Subfertility Induced by Heterozygous Expression of Catalytically Inactive Glutathione Peroxidase 4 Is Rescued in Vivo by Systemic Inactivation of the Alox15 Gene

Abstract: Glutathione peroxidase 4 (GPX4) and arachidonic acid 15-lipoxygenase (ALOX15) are antagonizing enzymes in the metabolism of hydroperoxy lipids. In spermatoid cells and/or in the male reproductive system both enzymes are apparently expressed, and GPX4 serves as anti-oxidative enzyme but also as a structural protein. In this study we explored whether germ line inactivation of the Alox15 gene might rescue male subfertility induced by heterozygous expression of catalytically silent Gpx4. To address this question w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Global knockout of Gpx4 results in early embryonic lethality, while conditional knockout of Gpx4 in specific organs (e.g., myeloid cells) is compatible with survival into adulthood. Conditional knockout models revealed that Gpx4 protects against experimental renal failure (Friedmann Angeli et al, 2014), neurodegenerative diseases (Chen et al, 2015), viral and parasitic infections (Matsushita et al, 2015), male subfertility (Brutsch et al, 2016), atherogenesis (Guo et al, 2008), anemia (Canli et al, 2016), and thrombus formation (Wortmann et al, 2013). Gpx4 depletion resulted in a marked elevation of apoptosis (Ran et al., 2003; Seiler et al, 2008), necroptosis (Canli et al, 2016), and ferroptosis (Friedmann Angeli et al, 2014; Yang et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Global knockout of Gpx4 results in early embryonic lethality, while conditional knockout of Gpx4 in specific organs (e.g., myeloid cells) is compatible with survival into adulthood. Conditional knockout models revealed that Gpx4 protects against experimental renal failure (Friedmann Angeli et al, 2014), neurodegenerative diseases (Chen et al, 2015), viral and parasitic infections (Matsushita et al, 2015), male subfertility (Brutsch et al, 2016), atherogenesis (Guo et al, 2008), anemia (Canli et al, 2016), and thrombus formation (Wortmann et al, 2013). Gpx4 depletion resulted in a marked elevation of apoptosis (Ran et al., 2003; Seiler et al, 2008), necroptosis (Canli et al, 2016), and ferroptosis (Friedmann Angeli et al, 2014; Yang et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas GPX4 has multiple molecular functions in the spermatozoa such as regulation of mitochondrial membrane potential, chromatin decondensation and detoxification of phospholipid hydroperoxides [39]. Besides, the moonlighting function of GPX4 (as an ROS metabolizing enzyme and structural protein), it is also responsible for the maintenance of mitochondrial stability and consequent male fertility [40]. GPX4 is also required for differential cell death decision in the testis [41] Sharma et al reported that the levels of GPX4 protein was upregulated in men with high seminal ROS [20].…”
Section: Discussionmentioning
confidence: 99%
“…Polyunsaturated fatty acids are known to stimulate ROS generation in human spermatozoa (Aitken, Wingate, De Iuliis, Koppers, & McLaughlin, ), and mammalian spermatozoa are known to possess lipoxygenase activity (Fischer et al, ). The fact that systemic inactivation of the Alox15 gene (encodes 15‐Lipoxygenase) can rescue the infertility phenotype observed in Gpx4 (Glutathione peroxidase 4)‐deficient mice suggests that the lipoxygenase system is somehow involved in the creation of oxidative stress within the male germ line (Brütsch et al, ). This conclusion is reinforced by the recent demonstration that ALOX15 is markedly up‐regulated in response to oxidative stress in round spermatids and in the GC‐2 cell line, whereas pharmacological inhibition of this enzyme reduces both ROS generation and 4‐hydroxynonenal accumulation in these cells (Bromfield et al, ).…”
Section: Physiological Sources Of Ros In Spermatozoamentioning
confidence: 99%